2022
DOI: 10.1037/pspp0000406
|View full text |Cite
|
Sign up to set email alerts
|

Affective contingencies of narcissism.

Abstract: Several theories propose that narcissism is rooted in affective contingencies. Given narcissists’ focus on power, these contingencies should be strong in the power domain but not in the affiliation domain. We systematically investigated narcissists’ contingencies and explored whether these contingencies might link narcissism to social behavior. In a multimethod longitudinal study, we assessed unidimensional narcissism levels as well as two main narcissistic strategies: Admiration and rivalry. We measured 209 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 114 publications
1
7
0
Order By: Relevance
“…Narcissistic rivalry and vulnerable narcissism were, in contrast, negatively related to affiliation-specific PACs, yet this pattern was only present for the PAC Rat scale. The findings thus indicate that grandiose narcissists’ pronounced tendency to seek power and their attenuated need for affiliation, which are well documented in the literature, might indeed go back to characteristic underlying motive-specific PACs (Grapsas et al, 2020, 2022). They also provide a first insight into the affective contingencies of vulnerable narcissism—namely, that vulnerable narcissists are characterized by attenuated affiliation-specific PACs—which could partly explain vulnerable narcissists’ tendency toward social isolation (Rogoza et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Narcissistic rivalry and vulnerable narcissism were, in contrast, negatively related to affiliation-specific PACs, yet this pattern was only present for the PAC Rat scale. The findings thus indicate that grandiose narcissists’ pronounced tendency to seek power and their attenuated need for affiliation, which are well documented in the literature, might indeed go back to characteristic underlying motive-specific PACs (Grapsas et al, 2020, 2022). They also provide a first insight into the affective contingencies of vulnerable narcissism—namely, that vulnerable narcissists are characterized by attenuated affiliation-specific PACs—which could partly explain vulnerable narcissists’ tendency toward social isolation (Rogoza et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…The model thus suggests that narcissistic admiration should go along with pronounced power-specific PACs and that narcissistic rivalry should be linked with attenuated affiliation-specific PACs. In partial support of these assumptions, Grapsas et al (2022) assessed motive-specific PACs via selfreports and experimental (EMG) assessments and found that narcissistic admiration and rivalry were both positively linked to self-reported power-specific PACs. The evidence based on the PAC EMG assessments did not uniformly support the predictions.…”
Section: Motive-specific Pacs and Their Relations To Motive Dispositi...mentioning
confidence: 99%
“…In a rigged video-game tournament, individuals with high narcissism tended to display more status-enhancing behaviors (rank buying) in response to victories and more combative behaviors (point stealing) in response to defeat (Szücs et al, 2022). On an emotional level, more narcissistic individuals displayed greater increases in positive affect after status satisfaction and greater increases in negative affect after status frustration (Grapsas et al, 2021(Grapsas et al, , 2022.…”
Section: Narcissism and Social Statusmentioning
confidence: 99%
“…In a rigged video-game tournament, individuals with high narcissism tended to display more status-enhancing behaviors (rank buying) in response to victories and more combative behaviors (point stealing) in response to defeat (Szücs et al, 2022). On an emotional level, more narcissistic individuals displayed greater increases in positive affect after status satisfaction and greater increases in negative affect after status frustration (Grapsas et al, 2021, 2022).…”
Section: Narcissism and Social Statusmentioning
confidence: 99%